Environmental and Housing-Related Risk Factors of Acute Respiratory Infection among Boarding House Students: A Case–Control Study in Minahasa Regency, Indonesia - Sudirham Sudirham; Tika Bela Sari (Pancasakti Journal Of Public Health Science And Research, 2026)
Acute Respiratory Infection (ARI) remains a major global health problem that affects all age groups, including young adults. University students living in boarding houses are potentially at higher risk due to crowded housing, poor ventilation, and unhealthy living behaviors. This study aimed to analyze the risk factors associated with ARI among boarding house students in Tataaran Patar, Minahasa Regency, North Sulawesi. A case–control study was conducted from May to September 2025, involving 68 respondents (34 ARI cases and 34 controls). Data were collected using structured questionnaires and analyzed using chi-square tests, with Odds Ratios (ORs) calculated to estimate the strength of associations. The results showed that room size (p=0.027, OR=3,040), presence of a kitchen inside the room (p=0.026, OR=3,125), and occupancy density (p=0.003, OR=4,866) were significantly associated with ARI incidence. In contrast, ventilation conditions (p=0.808, OR=0,888) and smoking behavior (p=0.808, OR=0,888) were not significantly associated with ARI. These findings indicate that room size, indoor kitchen facilities, and occupancy density are factors significantly associated with ARI among boarding house students in Tataaran Patar. Further studies using multivariate analysis are recommended to identify independent risk factors.